ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DAN SELF-EFFICACY SISWA SMP - Dea Damianti; Ekasatya Aldila Afriansyah (Program Studi Pendidikan Matematika FKIP Universitas Islam Darul Ulum, 2022)
Mathematics education is very important for survival, therefore students are expected to have good mathematical skills and attitudes, one of which is problem-solving ability and self-efficacy. The purpose of this study was to find out how the mathematical problem-solving ability of students in solving math problems on number pattern material and how the level of mathematical self-efficacy of class VIII students in Karamatwangi Village. The method used by the researcher is a qualitative research method. The sample in this study, namely class VIII B SMP IT Nurul Hidayah in Karamatwangi Village as many as 6 students based on predetermined categories, namely 2 people in the high category, 2 people in the medium category, and 2 people in the low category. The sampling technique used is the purposive sampling technique. The method of collecting problem-solving ability data is by providing several pattern material questions, conducting interviews, and documenting the results of the Final Semester Assessment, while the self-efficacy data collection method is by distributing questionnaires, conducting interviews, and making observations in field notes. The data analysis technique was carried out in several stages which included data reduction, data presentation, and conclusion. From the results of the study, it was shown that the mathematical problem-solving ability of class VIII junior high school students on the material of Number Patterns in Karamatwangi Village was in the high category and the self-efficacy level of class VIII junior high school students was in the high category.